Drivers of Fruit and Vegetable Intake Among Seniors in Bangkok, Thailand - Suvanbenjakule, Piraorn; Schreinemachers, Pepijn (2025)
Objectives: Seniors are at high risk due to inadequate intake of fruit and vegetables. Manifold factors influence this, but psychological and environmental factors have been understudied. This study fills this gap by analyzing drivers of intake among Bangkok seniors, combining demographic, food environment, and psychological variables using the Health Action Process Approach. Methods: A questionnaire with self-reported measures was used to interview 201 seniors from across Bangkok. The analysis uses multivariate regression and path analysis. Results: Average daily intake was found to be 267 grams, far below the WHO recommendation of 400 grams. Age and household size were associated with lower intake, while intention to consume, home cooking, and home gardening were associated with higher intake. However, the lack of significant effects for dental issues, nutritional knowledge, and planning challenges expectations and warrant further exploration. The path analysis also showed that planning did not mediate intention and intake as hypothesized. Reliance on habitual eating patterns among seniors may make typical meal planning less relevant. Conclusion: As the population ages and urbanizes, behaviorally informed public health strategies are needed to improve seniors' diet quality. Practical behavioral nudges and interventions targeting food vendors could support higher intake.